2012
DOI: 10.3109/13645706.2012.694367
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the OTSC System in the endoscopic closure of gastrointestinal fistulae - a meta-analysis

Abstract: Endoscopic closure of gastrointestinal fistulae by means of the OTSC System is a safe and effective method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…In the literature, we found some predictive criteria for fistula closure success using OTSC as follows: very early fistula (<7 days); fistulas with less fibrosis, leak size 10–30 mm; and leakages after LSG . Our work showed better efficiency of OTSC on fistulas after LSG ( P = 0.01), but we could not confirm the other factors.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In the literature, we found some predictive criteria for fistula closure success using OTSC as follows: very early fistula (<7 days); fistulas with less fibrosis, leak size 10–30 mm; and leakages after LSG . Our work showed better efficiency of OTSC on fistulas after LSG ( P = 0.01), but we could not confirm the other factors.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, new clipping devices such as OTSC (Ovesco Endoscopy, Tübingen, Germany) are recently being used as a good alternative to standard clips because one single clip allows steady closure of perforations ≤2.5 cm. In the clinical setting, the OTSC device has gained popularity during the past 6 years for its promising results in the sealing of digestive fistulas …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some favorable results by transanal approach using flexible colonoscopy with a newly developed clip [15,16] have been reported [17,18]. When we know to which type of fistula this kind of endoscopic treatment is appropriately indicated, this procedure should be regarded as minimally invasive choice of treatment and beneficial to the indicated patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, two factors have hindered researchers from comparing the various treatment modalities for closure of RVF, including the heterogeneity of the underlying etiologies causing RVF and the infrequency in which they occur. 3 One meta-analysis by Weiland et al found that using the OTSC system in the endoscopic closure of GI fistulae was safe, feasible, and had a clinical success rate of 69%. In addition, repeat OTSC procedures after initial clinical failure may further increase the success rate.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%